A Comparison of the Effects of Morphine and Sublingual Desmopressin Combination Therapy with Morphine Alone in Treatment of Renal Colic: A Controlled Clinical Trial - Keshvari Shirvani, Maliheh; Darabi Mahboub, Mohammadreza; Ghazi, Mahdi; Delijani, Alireza (Urology Journal, 2015)
Abstract Purpose: To compare the therapeutic efficacy of combined desmopressin and morphine with morphine and placebo on acute renal colic. Materials and Methods: In a single blind case-control clinical trial 81 consecutive patients, 54 males and 27 females with the mean age of 30.12 ± 9.88 years, presenting with acute renal colic to the urology emergency unit were studied. The patients were randomly assigned into two groups. The 40 cases were treated with 0.1 mg/kg IM morphine and 60 μg of sublingual desmopressin melt; whereas the 41 controls received the same dose of morphine beside a placebo. Results: There were no significant statistical differences regarding the mean age, gender, stone size, location and affected side between the two groups. Our results showed a significantly higher acuity of pain in the study group in comparison to the controls at 10, 20 and 30 minutes of receiving the medication (P = .06, .017 and P = .008, respectively). Conclusion: No superiority was found in adding desmopressin to morphine compared to the traditional treatments (opioids only) in relieving the pain of acute renal colic cases.